Transfer RNA and human disease - Abbott, Jamie A.; Francklyn, Christopher S.; Robey-Bond, Susan M. (Frontiers in Genetics, 2014)
Pathological mutations in tRNA genes and tRNA processing enzymes are numerous and result in very complicated clinical phenotypes. Mitochondrial tRNA (mt-tRNA) genes are “hotspots” for pathological mutations and over 200 mt-tRNA mutations have been linked to various disease states. Often these mutations prevent tRNA aminoacylation. Disrupting this primary function affects protein synthesis and the expression, folding, and function of oxidative phosphorylation enzymes. Mitochondrial tRNA mutations manifest in a wide panoply of diseases related to cellular energetics, including COX deficiency (cytochrome C oxidase), mitochondrial myopathy, MERRF (Myoclonic Epilepsy with Ragged Red Fibers), and MELAS (mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes). Diseases caused by mt-tRNA mutations can also affect very specific tissue types, as in the case of neurosensory non-syndromic hearing loss and pigmentary retinopathy, diabetes mellitus, and hypertrophic cardiomyopathy. Importantly, mitochondrial heteroplasmy plays a role in disease severity and age of onset as well. Not surprisingly, mutations in enzymes that modify cytoplasmic and mitochondrial tRNAs are also linked to a diverse range of clinical phenotypes. In addition to compromised aminoacylation of the tRNAs, mutated modifying enzymes can also impact tRNA expression and abundance, tRNA modifications, tRNA folding, and even tRNA maturation (e.g., splicing). Some of these pathological mutations in tRNAs and processing enzymes are likely to affect non-canonical tRNA functions, and contribute to the diseases without significantly impacting on translation. This chapter will review recent literature on the relation of mitochondrial and cytoplasmic tRNA, and enzymes that process tRNAs, to human disease. We explore the mechanisms involved in the clinical presentation of these various diseases with an emphasis on neurological disease.